Jewishness and beyond : Jewish conversions in Hungary 1825-1914 - Konrád, Miklós (Studies in Hungarian history., 2024)
""Konrád's monograph is clearly written and organized well by theme and chronology. ... [I]t treats exhaustively the subject and gives different kinds of information: statistics, anecdotes, analysis and from each side-the Jewish viewpoint, non-Jews, church leaders and politicians. Very well-argued book." - Brian Horowitz, author of Vladimir Jabotinsky's Russian Years, 1900-1925 During the nineteenth century tens of thousands of Hungarian Jews converted to various Christian denominations, starting in the Reform Era (1825-1848). Yet this first significant wave of conversion, and those that followed, coincided with an increasing decline in the formal disadvantages of belonging to Hungary's Jewish community. By the turn of the twentieth century Hungary's Jews could no longer be described as pariahs in a legal sense, yet the rate of conversion continued to grow in the next two decades. Addressing this apparent paradox in the first monographic treatment of the topic, Konrád examines conversion from numerous unique sources-registers, statistics, community archival materials, synagogue speeches, parliamentary diaries, daily newspapers, magazines, calendars, association yearbooks, brochures, correspondence, diaries, memoirs, biographies, works of fiction, collections of jokes, and more. He finds that between 1848 and 1914, most of the Hungarian Jews who converted to Christianity were motivated by worldly concerns; that despite the egalitarian promises and laws of Hungary's liberal nationalist government, legislators and other traditional elites maintained a persistent bias against Jews that spurred particularly high conversion rates among the community's upper echelons; and that while Christians never fully forgot converted Jews' origins and increasingly thought of them in racialized terms, they also appreciated and generally rewarded conversion and the symbolic gesture of baptism. Conversion was also an uneven and ever-shifting process in which gender and occupation played key roles, and where the actual percentage of converts vis-à-vis the total Hungarian Jewish population contrasted sharply with both Christian and Jewish perceptions of its frequency and spread. Jewishness and Beyond reveals the motivations and strategies behind Hungarian Jews' conversions, the complex reactions within and outside of their communities, and converts' own grappling with conversion's expected and unforeseen outcomes"--